Bone Regulates Glucose Metabolism as an Endocrine Organ through Osteocalcin. (19th March 2015) - Shao, Jin; Wang, Zhi; Yang, Tieyi; Ying, Hui; Zhang, Yan; Liu, Shuyi
Abstract : Skeleton was considered as a dynamic connective tissue, which was essential for mobility, calcium homeostasis, and hematopoietic niche. However more and more evidences indicate that skeleton works not only as a structural scaffold but also as an endocrine organ, which regulates several metabolic processes. Besides osteoprotegerin (OPG), sclerostin (SOST), and Dickopf (DKK) which play essential roles in bone formation, modelling, remodelling, and homeostasis, bone can also secret hormones, such as osteocalcin (OCN), which promotes proliferation of β cells, insulin secretion, and insulin sensitivity. Additionally OCN can also regulate the fat cells and male gonad endocrine activity and be regulated by insulin and the neural system. In summary, skeleton has endocrine function via OCN and plays an important role in energy metabolism, especially in glucose metabolism.